Destabilizing Binaries: Atta Shad’s Use of Paradoxical Symbols in Modern Balochi Poetry - Dr. Adnan Riaz; Dur Jan; Zoha (`, 2025)
The paper analyses Atta Shad’s paradoxical symbols in some of his poems in order to underline his unique contribution to modern Balochi poetry. Contrary to earlier critics who focused on some dominant thematic focal points of Shad’s poetry, this study concentrates on the symbolic and deconstructive forms of his poetic imagery. Focusing closely on such poems as Kadi Beet Man Nazana Mani Aagahi Cha Waaba, Bita Kadi Nabeete, and Saah Kandan, the paper interrogates how Shad reconfigures the traditional pictorial and verbal signs associated with life, death, virtue, and divinity, and deploying paradoxical signs, he defamiliarizes any entrenched meaning, and pushes the reader to encounter reality from a relative and post-modern perspective. The analysis shows that Shad’s symbolic order not only reflects human struggle and cultural consciousness but also opens new ways of understanding “existence” through a fluid and changing context in modern Balochi literature. Keywords: Atta Shad, Symbolism, Postmodernism, Paradoxical Symbols, Balochi Poetry